Diagnostic Performance of Initial Transperineal Template-guided Mapping Biopsy of the Prostate Gland. (June 2015) - Bittner, Nathan; Merrick, Gregory S.; Bennett, Abbey; Butler, Wayne M.; Andreini, Hugo J.; Taubenslag, Walter; Adamovich, Edward
<x xml:space="preserve">Abstract</x> Objectives: To evaluate the utility of transperineal template-guided mapping biopsy (TTMB) of the prostate as an initial means of establishing tissue diagnosis. Materials and Methods: A total of 191 consecutive patients underwent TTMB of the prostate using an anatomic-based technique with sampling of 24 regions. All patients had elevated prostate-specific antigen on routine screening which was followed by a confirmatory prostate-specific antigen and none had undergone previous biopsy of the prostate. The locations of cancer involvement were recorded for each patient in an effort to approximate the percentage of men whose cancer would have been missed or Gleason score underestimated on a standard 12-core biopsy. The median number of submitted biopsy cores was 54.0. Results: Of the 191 study patients, 140 (73.3%) were diagnosed with cancer on TTMB. Among these biopsy-positive patients, 124 (88.6%) had clinically significant cancer. Eighty-nine of the biopsy-positive patients (64.6%) had a Gleason score of ≥7. A total of 34 of the 140 diagnosed cancers were identified exclusively in regions that fell outside of the theoretical 12-core biopsy scheme, suggesting that 24.3% of these cancers would have gone undiagnosed in the absence of TTMB. Among the 107 cancers that would have been diagnosed using a 12-core biopsy approach, 18 (16.8%) were upgraded to a Gleason score of ≥7 with mapping biopsy. Conclusions: TTMB appears to provide more detailed information about prostate cancer grade and location compared with standard 12-core biopsy scheme. This information may serve as a baseline reference for image-guided biopsy (ie, magnetic resonance imaging) regimens, may facilitate clinical decision making and aid in the appropriate selection of patients for active surveillance.